Implementing a Scientifically Valid, Cost-Effective, and Scalable Data Collection System at Point of Care: The Cleveland Clinic OME Cohort. (6th March 2019) - Piuzzi, Nicolas S.; Strnad, Greg; Brooks, Peter; Hettrich, Carolyn M.; Higuera-Rueda, Carlos; Iannotti, Joseph; Kattan, Michael W.; Molloy, Robert; Lynch, T. Sean; Milinovich, Alex; Ricchetti, Eric T.; Rosneck, James; et al.
Abstract : Background: Improving outcomes after surgical procedures and determining the value of health care can be facilitated by a scientifically valid, cost-effective, and scalable data outcome collection system. We hypothesized that such a system could be constructed in orthopaedic surgery to (1) capture >95% of baseline validated patient-reported outcome measures (PROMs) for patients undergoing elective surgery, (2) capture >95% of surgeon-entered data on disease severity and treatment, and (3) be implemented as standard clinical care in daily practice. Methods: A modified Research Electronic Data Capture (REDCap) system was developed and was implemented at the time of surgery in a prospective cohort to collect demographic data, general health PROMs, joint-specific PROMs, and disease severity and treatments from patients and surgeons. All elective knee, hip, and shoulder orthopaedic surgical procedures performed in the Cleveland Clinic system at 7 hospitals were included. Results: Of 16, 021 consecutive eligible patients (February 18, 2015, to July 31, 2017), 2% (320) were excluded because of language or physical barriers, and 0.6% (91) of the remaining 15, 701 patients refused to participate. Of the remaining 15, 610 patients, 97.4% (15, 202) completed PROMs, and surgeons provided details on the disease severity and treatment for 99.9% (15, 592) of the 15, 610 patients. Overall, 97.3% (15, 185) of the 15, 610 patients had complete patient-reported and surgeon-reported baseline enrollment. The median completion time was 11.5 minutes for the patients and 1.6 minutes for the surgeons. The overall complete 1-year follow-up rate was 72.5% (9, 354 of 12, 896). Conclusions: A data collection system with validated measures with >97% baseline completion of PROMs and surgeon forms regarding disease severity and treatments, across elective knee, hip, and shoulder orthopaedic surgical procedures, was successfully implemented at 7 hospitals. The system is potentially scalable to the entire orthopaedic community and could serve as a template for all procedural-based specialties during routine patient care.